Reimagining equity: redressing power imbalances between the global North and the global South. Issue 1 (2nd January 2020) - Martins, Alex
ABSTRACT: Equity in development is most often used to describe something the global North does to or in the global South, rather than as a concept that applies between the North and South. Neither does it take into consideration the issue of creating systems that foster equity between the North and the South, within the context of historical inequalities and power dynamics. This article examines equity in development from four different perspectives: language, knowledge production, funding, and partnerships, recognising that if we are to reimagine development in a genuine rather than a cosmetic way, we need to address the root causes behind global inequity and grapple with entrenched power imbalances. By explicitly using the term 'equity' in the context of re-imagining the global development system, we both acknowledge this reality and make explicit the fact that a rebalancing of power relations and global resources is necessary if we are to achieve a more equal global system.